How to Calculate Economic Evaluation in Industrial Chemical Plant Design: A Case Study of Gold Mining Using Amalgamation Method - Fiandini, Meli; Nandiyanto, Asep Bayu Dani (Bumi Publikasi Nusantara, 2024)
In the world of the chemical industry which continues to develop, factory design is the first step that determines the success of a project. However, to ensure that sustainability, efficiency and a positive impact on the economy can be achieved, economic evaluation is a critical aspect that must be considered carefully. Economic evaluation has a central role in the design stage of industrial chemical plants. However, until now, there is still no research that explains step by step how to calculate economic evaluations, especially in the field of industrial chemistry. Based on this, the aim of this article is to demonstrate how to calculate economic evaluations in chemical plant design. To provide a detailed understanding, we present a step-by-step example of calculating an economic evaluation of the design of a gold mining using amalgamation method. It is hoped that this article can have a significant impact by illustrating effective ways to optimize financial sustainability, make wise data-based decisions, and manage risk carefully in the design of industrial chemical plants through in-depth analysis using economic evaluation. Here, this article not only serves as an important basis for corporate decision-making, but also provides valuable guidance for the chemical industry in designing efficient and economically sustainable production facilities.